Role of nanoparticles in osteogenic differentiation of bone marrow mesenchymal stem cells - Mahmoud, Nadia S. (Cytotechnology, 2019)
The present study aimed to investigate the osteoinductive potentiality of some selected nanostructures; Hydroxyapatite (HA-NPs), Gold (Au-NPs), Chitosan (C-NPs), Gold/hydroxyapatite (Au/HA-NPs) and Chitosan/hydroxyapatite (CH-NPs) on bone marrow- derived mesenchymal stem cells (BM-MSCs). These nanostructures were characterized using transmission electron microscope and Zetasizer. MSCs were isolated from bone marrow of rat femur bones and their identity was documented by morphology, flow cytometry and multi-potency capacity. The influence of the selected nanostructures on the viability, osteogenic differentiation and subsequent matrix mineralization of BM-MSCs was determined by MTT assay, molecular genetic analysis and alizarin red S staining, respectively. MTT analysis revealed insignificant toxicity of the tested nanostructures on BM-MSCs at concentrations ranged from 2 to 25 µg/ml over 48 h and 72 h incubation period. Notably, the tested nanostructures potentiate the osteogenic differentiation of BM-MSCs as evidenced by a prominent over-expression of runt-related transcription factor 2 (Runx-2) and bone morphogenetic protein 2 (BMP-2) genes after 7 days incubation. Moreover, the tested nanostructures induced matrix mineralization of BM-MSCs after 21 days as manifested by the formation of calcium nodules stained with alizarin red S. Conclusively, these data provide a compelling evidence for the functionality of the studied nanostructures as osteoinductive materials motivating the differentiation of BM-MSCs into osteoblasts with the most prominent effect observed with Au-NPs and Au/HA-NPs, followed by CH-NPs.